PROSES PENILAIAN ASET DAERAH DALAM SIKLUS PENGELOLAAN BARANG MILIK DAERAH DI DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET (DPPKA) KABUPATEN SUMENEP - Sucipto, Moh. (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2016)
This study aims to know the assessment process of the regional assets in the regional asset management in the Department of Revenue, Management Finance and Asset (DPPKA) Sumenep Regency. In this observation, the author uses qualitative descriptive approach with primary and secondary data sources. The process of data collection techniques of this thesis with the observation, interviews, and documentation. The conclusions of this obserbetion is the process of regional assets assessment in the regional property management in DPPKA Sumenep regency has generally been in accordance with the laws and regulations on the management of the State of regional property, the implementation of the assessment in Sumenep Regency technically implemented by external parties